Tic disorders and the premonitory urge - Steinberg, Tamar (Springer Vienna, 2009)
The aims of this study were to examine a non-English (Hebrew) version of a scale that measures the premonitory urge in children suffering from tic disorder, as well as examine the correlations of the urge with demographic and clinical aspects of Tourette Syndrome. Forty children and adolescents, suffering from tics participated in this study. They were assessed with the Premonitory Urge for Tics Scale (PUTS); the Yale Global Tic Severity Scale (YGTSS); the Childhood Version of the Yale Brown Obsessive Compulsive Scale (CYBOCS); the ADHD Rating Scale IV (Conners) Scale; the Screen for Child Anxiety Related Emotional Disorders (SCARED); and the Child Depression Inventory (CDI). The mean PUTS score was 20.15 (SD = 5.89). For the entire sample the PUTS was found to be internally consistent at a = 0.79. Youths older than 10 years had higher consistency (a = 0.83) than youths younger than 10 (a = 0.69). Premonitory urge was not correlated with tic severity in the entire sample. In youths older than 10, as opposed to youths younger than 10, premonitory urge did correlate with obsessions, compulsions and depression, but not with anxiety or with ADHD. The premonitory urge can be measured reliably and the PUTS is a useful instrument for measuring this important phenomena. Premonitory urges seems to be related to obsessions, compulsions, and depression in older children and this may have implications for the developmental psychopatholgy of these symptoms.